The expression profile of human peripheral blood mononuclear cell miRNA is altered by antibody-dependent enhancement of infection with dengue virus serotype 3 - Liming Jiang; Qiangming Sun (Virology Journal, 2018)
Abstract Background Antibody-dependent enhancement (ADE) of dengue virus (DENV) infection has been identified as the main risk factor for severe dengue disease, although the underlying mechanisms leading to severe dengue fever remain unclear. MicroRNAs (miRNAs) participate in numerous pathological and biological processes, including host responses to viral infections. Method Here, we aimed to investigate the differences in miRNA expression patterns in human peripheral blood mononuclear cells (PBMCs) infected with DENV-3 and DENV-3-ADE at various time points employing high-throughput sequencing. Results According to miRNAs high-throughput sequencing, a total of 50 known miRNAs exhibited significant differences. GO (Gene Ontology) and pathway analysis of the predicted targets showed enrichment in the regulation of transcription, including multicellular organismal development, DNA-dependent transcription, negative regulation of cell differentiation and transcription. Afterwards, regulatory networks of miRNA predicted targets, miRNA transcription factors, miRNA pathways and miRNA GOs were formulated to expose the complex regulatory mechanisms of miRNAs during the infection phase. Finally, we analyzed hierarchical GO categories of the predicted targets involved in the MAPK signaling pathway, the cGMP-PKG signaling pathway, the cAMP signaling pathway, the endocytosis effect, and our analyses indicated that innate and adaptive immunity following DENV-3 and DENV-3-ADE infections may be signally distinct. Conclusion Our results demonstrate a novel describing miRNA expression profiles in human PBMCs with DENV-3 and DENV-3-ADE infections using high-throughput sequencing. Our findings could provide a beneficial basis for further studies on the regulatory roles of miRNAs relevant to the different immune responses caused by DENV-3 and DENV-3-ADE infections.